"I like to get my hands stuck in the soil": A pilot study in the acceptance of soil-less methods of cultivation in community gardens. (10th June 2020) - Caputo, Silvio; Rumble, Heather; Schaefer, Martin
Abstract: The aim of this paper is to investigate the role that soil-less methods of food production can play in urban agriculture, particularly in projects that are run by community groups. Over the last years, a drive by people to engage in sustainable lifestyles has resulted in a surge in urban agriculture. Typically, on-soil horticulture is greatly appreciated by urban farmers for its invaluable contribution to urban ecology. Yet, some community projects across Europe are experimenting with indoor soil-less methods, which offer an opportunity to reduce the waste of resources such as water and space, including valuable greenspace. Against this backdrop, the paper investigates the drivers and barriers that may facilitate or hinder soil-less methods for urban farmers. We triangulate information from the literature with a small-scale pilot study, based on interviews in a community garden in Portsmouth, UK, in which a small hydroponic unit was utilised by a group of experienced farmers. We subsequently compare results with a previous pilot study, similar in design but with interviewees who have limited experience in growing food. Qualitative results show a general appreciation of the environmental advantages that the hydroponic unit can yield and at the same time diffidence towards a hydroponic produce which is perceived as non-natural in both groups. Quantitative analysis showed that 90% of experienced farmers had prior knowledge of soil-less methods against 42% of the wider sample group. We conclude that, for the participants to the pilots, higher knowledge of soil-less systems does not necessarily lead to higher acceptance. Yet, feedback gathered suggests that there is interest in soil-less methods, which appears to be linked to the propensity of community gardens to test new arrangements and techniques within their projects. Graphical abstract: Image 1002898 Highlights: Factors preventing use of hydroponics in urban agriculture are poorly understood. Hindering factors include use of chemicals and hydroponics perceived as non-natural. Hindering factors are stronger amongst experienced urban gardeners. Awareness of overall environmental benefits of hydroponics can combat reservations.